TEACHERS’ KNOWLEDGE ABOUT HIGHER ORDER THINKING SKILLS AND ITS IMPLEMENTATION IN ONLINE TEACHING - Desi Futriana (Corolla International Conference, 2022)
Higher-order Thinking Skills (HOTS) is a concept that is being debated by researchers, particularly in the context of education. Teachers are expected to develop materials that enable the students to have higher order thinking skills, increase their creativity, and build students’ autonomy in solving the problem. The ability of students to think with HOTS in the teaching and learning process is a difficult assignment for teachers to do. The classroom process and assessment are designed to meet the students’ needs of improving their HOTS Teachers must expand their knowledge of HOTS in order to provide optimal and successful online instruction. The goal of this study is to look into teachers’ knowledge of HOTS and how they use it in online teaching. This is a qualitative study, and the research design is a case study. The information was gathered through in-depth interviews and observation. The participants of this research were three English teachers from a senior high school who teach different grades. The findings found that teachers failed to clearly communicate the concept of thinking and thinking processes, and that the majority of teachers were unable to explain HOTS as critical and creative thinking. However, their use of HOTS in the online classroom revealed that they use it to help students activate their HOTS